HUBUNGAN PAPARAN DEBU DAN LAMA PAPARAN DENGAN GANGGUAN FAAL PARU PEKERJA OVERHAUL POWER PLANT - Kiky Aunillah Yolanda Ardam (Universitas Airlangga, 2015)
ABSTRACTDust exposure in the working environment is a potential factor to cause lung function disorders. Lung function disorders such as restriction, obstruction, and mixed-type which is indicated by decreasing % FEV and % FVC. Overhaul power plant workers have high risk dust exposure in the working environment as impact of the process overhaul power plant machine. Dust from overhaul work can entry to the respiratory tract of the workers through inhalation. The purpose was to analyze the relationship of total dust exposure and exposure time with lung function disorder among overhaul power plant workers in PT. PJB Unit Pelayanan Pemeliharaan Wilayah Timur. This research was an observational analytical study with cross sectional design. The sample size was 32 which were taken by simple random sampling technique. Relationship between dust exposure and exposure time with lung function disorders was analyzed statistically by using Chi Square Test (χ2). The study found that only dust exposure was significantly relationship with lung function disorders (p = 0.006 < α = 0.05) and the most prevalence of lung function disorders was mixed-type lung function impairment. It is recommended that the company provide Local Exhaust Ventilation (LEV) at the sources of contaminant (dust) and reduce the exposure time.Keywords: dust exposure, exposure time, lung function disorders, overhaul